Evolution of sun‐protection measures for children. (February 2015) - Lebbé, C.; Robert, C.; Ricard, S.; Sassolas, B.; Grange, F.; Saiag, P.; Lhomel, C.; Mortier, L.
Abstract: Background: The prevention of melanoma can be significantly improved by targeting information directly towards the subpopulation of children and, as a means to achieve it, towards young parents. Objectives: The objective of this analysis was to determine the evolution over time of the sun‐protection measures adopted by parents for their young children. Methods: The Edifice Melanoma survey was based on telephone interviews of a representative sample of 1502 subjects aged ≥18 years. This particular analysis focuses on 864 adults whose children are exposed to the sun for more than 10 days a year. We compared the characteristics and attitudes of two sub‐groups of parents with regard to sun protection of young children: current‐day behaviour of parents with children <15 years and behaviour in the past of parents whose children are now ≥15 years. Results: Present‐day parents are more likely than those of previous generations to systematically or often use hats (96% vs. 90%, P < 0.01), protective clothes (92% vs. 84%, P < 0.01), sunscreen (89% vs. 80%, P < 0.01) and sunglasses (63% vs. 44%, P < 0.01) for their children. Systematic application of sunscreen is also more frequent today than several years ago as reported by 81% of present‐day parents vs. 74% of those in the past ( P < 0.05). Cream is reapplied every 2 h by 41% of present‐day parents, compared to 33%, in the past ( P < 0.05). Conclusions: The attitude of parents towards sun protection for their children has improved over the past decade.